Proof of Concept of the Electrochemical Sensing of 3‐Iodothyronamine (T1AM) and Thyronamine (T0AM). Issue 10 (25th August 2014) - Gonçalves, Luís M.; Moreira, Manuela M.; Azevedo, Carla F.; Valente, Inês M.; Sousa, João C.; Scanlan, Thomas S.; Compton, Richard G.; Rodrigues, José A.
Abstract Recent studies have shown that, besides the well‐recognized T3 and T4 hormones, there are other relevant thyroid hormones circulating in the human body. In particular, this is the case for 3‐iodothyronamine (T1AM) and thyronamine (T0AM). One of the reasons for the lack of studies showing their precise importance is the absence of analytical methodologies available. Herein, for the first time, T1AM and T0AM are electrochemically characterized. T0AM was sensed by means of a glassy carbon electrode; furthermore, T1AM was sensed both with a graphitic surface (oxidatively) as well as with mercury (reductively). For both compounds, after oxidation, it was possible to observe the reversible redox reaction concerning the benzoquinone/hydroquinone couple, thus increasing the specificity of the electroanalysis. Therefore, this work provides the basis for an 'at‐point‐of‐use' electrochemical strip test for T1AM and T0AM.